2021
DOI: 10.1002/biot.202100030
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of nosocomial transmission and biofilm formation on novel biocompatible antimicrobial gloves impregnated with biosynthesized silver nanoparticles synthesized using Eucalyptus citriodora leaf extract

Abstract: Failure in the prevention of cross‐transmission from contaminated gloves has been recognized as an important factor that contributes to the spread of several healthcare‐associated infections. Ex situ coating process with silver nanoparticles (AgNPs) using Eucalyptus citriodora ethanolic leaf extract as reducing and capping agents to coat glove surfaces has been developed to prevent this mode of transmission. Elemental analysis of coated gloves showed 24.8 Wt% silver densely adhere on the surface. The coated gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The synthesized AgNPs showed good antimicrobial activities with no cytotoxic effects on HeLa cells (Wunnoo et al 2021). Green-synthesized AgNPs have been studied for applications in food packaging materials (Nwabor et al 2020), and have been used as a coating agent on gloves to prevent microbial transmission (Paosen et al 2021), and on sutures to prevent surgical site infections (Syukri et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The synthesized AgNPs showed good antimicrobial activities with no cytotoxic effects on HeLa cells (Wunnoo et al 2021). Green-synthesized AgNPs have been studied for applications in food packaging materials (Nwabor et al 2020), and have been used as a coating agent on gloves to prevent microbial transmission (Paosen et al 2021), and on sutures to prevent surgical site infections (Syukri et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The elemental analysis of the coated gloves revealed that 24.8% wt silver was firmly adhered to the surface. Biofilms of S. aureus ATCC 25923, P. aeruginosa ATCC 27853, and Candida albicans ATCC 90028 were expected to develop on glove samples during 24 h of incubation [121].…”
Section: Nr Gloves With Sio 2 and Zno Hybrid Nanofillersmentioning
confidence: 99%
“…Images from fluorescence microscopy were stained with a red fluorescent DNA-specific dye that only penetrates cells with damaged membranes and dead bacteria. The pictures revealed that P. aeruginosa cells were significantly less abundant and viable when cultured on AgNP-coated gloves compared to uncoated gloves, suggesting that AgNPs killed and inhibited microbial adhesion [121].…”
Section: Nr Gloves With Sio 2 and Zno Hybrid Nanofillersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the toxicity evaluation approach was based on ISO 10993:5, which establishes the methodology for the in vitro assessment of the cytotoxicity of medical devices and other materials [ 23 ], being also frequently used to assess the toxicity of antimicrobial coatings and materials [ 24 , 25 ]. Following the recommendations of ISO 10993:5, tests by direct contacts and tests on extracts were performed for cytotoxicity evaluation.…”
Section: Introductionmentioning
confidence: 99%